IMPLEMENTASI MEDIA PEMBELAJARAN PUZZLE PADA MATA PELAJARAN PAI MATERI AL-KHULAFAUR AR-RASYIDIN KELAS VII SMP DARUSSYAFA’AH, SETAIL-GENTENG - Muttaqin, Ahmad Izza; Nasrodin, Nasrodin; Humairoh, Siti (Ar-Risalah: Media Keislaman, Pendidikan dan Hukum Islam, 2021)
This study aims to explain the implementation of puzzle learning media in PAI subjects with the material of Al-Khulafaur Ar-Rashidin Class VII Darussyafa'ah Middle School, Setail-Genteng for the 2020/2021 Academic Year. This type of descriptive qualitative research. Data collection methods are passive participation observation, semi-structured interviews, and documentation. The subject of the study was PAI teachers, students of class VII. The validity of the triangulated data. Data analysis includes data collection, data reduction, data presentation, verification. The results of the study, PAI educators use three components in learning, planning, implementation, and assessment (evaluation). Lesson planning prepares the syllabus, lesson plans, and subject matter. The implementation of learning is in accordance with the steps of the puzzle learning media. And for evaluation/assessment, write tests, remedials, and evaluations are carried out in the middle of the semester and at the end of the semester. Inhibiting factors, lack of motivation of students in studying religious education, varied learning styles, students who lack confidence, are not maximally applied in large groups, only exist in schools, and require special care in storing them. Supporting factors, the sense of interest in learning and the curiosity of students to use puzzle media, the size is not too large, students can see, observe and conduct experiments and add insight, teachers are creative, teacher abilities, appropriate learning models, and student responses good.